2019
DOI: 10.1186/s13567-019-0628-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of contagious caprine pleuropneumonia reveals the ability of convalescent sera to reduce hydrogen peroxide production in vitro

Abstract: Contagious caprine pleuropneumonia (CCPP), caused by Mycoplasma capricolum subsp. capripneumoniae is a severe disease widespread in Africa and Asia. Limited knowledge is available on the pathogenesis of this organism, mainly due to the lack of a robust in vivo challenge model and the means to do site-directed mutagenesis. This work describes the establishment of a novel caprine challenge model for CCPP that resulted in 100% morbidity using a combination of repeated intranasal spray infection followed by a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…This model is based on a combination of two subsequent inoculations of aerosols of cultures into the nasal cavity of goats followed by a trans-tracheal inoculation. Morbidity of 100% and a mortality of 50-60% was seen in infected animals, closely mimicking natural infection 49 . Improvements of the challenge model are possible, including titration of the challenge dose, use of an aerosol chamber for infection as has been used for experimental infections with other Mycoplasma species 51,52 , and whether either the aerosol or the trans-tracheal inoculations are dispensable to allow simplification of the procedure.…”
Section: Research Gaps To Be Addressedmentioning
confidence: 56%
See 3 more Smart Citations
“…This model is based on a combination of two subsequent inoculations of aerosols of cultures into the nasal cavity of goats followed by a trans-tracheal inoculation. Morbidity of 100% and a mortality of 50-60% was seen in infected animals, closely mimicking natural infection 49 . Improvements of the challenge model are possible, including titration of the challenge dose, use of an aerosol chamber for infection as has been used for experimental infections with other Mycoplasma species 51,52 , and whether either the aerosol or the trans-tracheal inoculations are dispensable to allow simplification of the procedure.…”
Section: Research Gaps To Be Addressedmentioning
confidence: 56%
“…A common feature of these models is the intratracheal inoculation of a Mycoplasma culture using a tube that is inserted via the nasal or oral cavity while the animal is standing or in lateral recumbency. In the past, fresh cultures were used for inoculation, however, it has now been demonstrated that frozen stock cultures work well for both pathogens 60,49 . The instillation of a solution of agar after inoculation of the mycoplasma broth culture has been show to be dispensable 60 .…”
Section: Research Gaps To Be Addressedmentioning
confidence: 99%
See 2 more Smart Citations
“…It is against this background that this work reports the use of an invivo experiment, comparing a wild type (Mmc GM12) and Mmc 1.1 delta 68 strains to ascertain whether the mutant after target specific edits led to attenuation. This alternative method was adopted with modifications for other ruminant Mycoplasma in-vivo work by Jores et al (2018) and Liljander et al (2019), with infection success observed.…”
Section: Discussionmentioning
confidence: 99%